Service Diversification Strategies and Performance of Hospitality Industry in Rwanda: A Case of Centre National d’Education Transformatrice (CENETRA) - Christine , Turabamariya; Irechukwu, Eugenia Nkechi (Journal of Strategic Management, 2022)
In current competitive, changing business world, with the aim to increase performance firms are constantly struggling to satisfy various needs of customers and maintain a competitive advantage in the market. As a strategic alternative, diversification is used by business organisations targeting to outpace new entrant and or existing firms. The main objective of this study is to examine the influence of service diversification strategy on organisational performance of hospitality industry in Rwanda. From the main objective the researcher derived three concise targets pointing to three types of diversification strategy. The targets were to determine consecutively the influence of concentric, horizontal and conglomerate strategies on the performance of CENETRA Hotel. Findings of this research are useful to hotels and other accommodation establishments owners who intend to gain a competitive advantage, sustain and grow their businesses diversifying their services. The research results will inform the Private Sector Federation (PSF) and Rwanda Development Board (RDB) on priorities to be considered in developing hospitality business sector. Moreover it will broaden research field and the domain of diversification strategies where influence of a variety of services can have on firm’s performance. Descriptive design also known as statistical design and analytical design was used by the researcher. This study targeted 54 staff members, 4 management team members CENETRA Hotel and 47 permanent customers at CENETRA. It adopted probability stratified, random and purposive sampling technics. Questionnaires and interviews were used to collect primary information and documentary review was applied to collect secondary data and SPSS version 21 was used for data analysis. Descriptive statistics with the mean, standard deviation, and Pearson’s correlation coefficient were utilised and inferential statistics with regression analysis were applied for data interpretation. Findings revealed that concentric diversification strategy is very highly correlated with organisational performance with Pearson’s correlation value= 0.935, p value=0.001<0.05. Moreover results uncovered that horizontal diversification strategy is significantly positively correlated organisational performance. A mean of 38% of total respondents strongly agreed, 57% agreed, with presented statements with a correlation coefficient value of 0.929 p=0.004<0.05. Conglomerate diversification strategy is positively correlated to organisational performance as quantified by Pearson’s correlation coefficient of 0.725 p=0.002<0.05. These statistical figures were supported by four managers answers of interview who affirmed that service diversification strategies has a positive influence on performance of hospitality industries in Rwanda. Thus the research established that service diversification strategy highly influence the performance of hospitality industries in Rwanda. It is recommended to hospitality organisations to diversify their services implementing concentric, horizontal and conglomerate diversification strategies, to PSF and RDB to consider service diversification strategies in policy making in order to strengthen more hospitality industry in Rwanda. Key words: Service Diversification Strategy, Hospitality, Organizational Performance